Rediscovery of Eugenia fajardensis (Myrtaceae), a rare tree from the Puerto Rican Bank - Trejo-Torres, Jorge Carlos; Caraballo-Ortiz, Marcos A.; Vives-Heyliger, Miguel A.; Torres-Santana, Christian W.; Cetzal-Ix, William; Mercado-Díaz, Joel A.; Carlo, Tomás A. (Phytotaxa, 2014)
Eugenia fragrans var.? fajardensis was described in 1895 and raised to species status in 1923 as E. fajardensis. In 1925, it was relegated to the synonymy of Anamomis fragrans (Myrcianthes fragrans). Since 2001, we have re-discovered wild plants and herbarium specimens, including a previously unidentified isotype of E. fajardensis, supporting the validity of this species. Here we designate a lectotype and an epitype for E. fajardensis. In addition, we provide: 1) an extended description for the species including the previously unknown flowers and fruits, an illustration, and photographs of live plants, 2) a key for the 24 taxa of Eugenia reported for Puerto Rico and the Virgin Islands, and 3) descriptions of the three known populations. These populations collectively hold 182 plants in the islands of Puerto Rico, Culebra, and Vieques. Based on the IUCN Red List Criteria, E. fajardensis meets the requirements to be considered a Critically Endangered species.